Case report: Report of a case of female adnexal malignant tumor of Wolffian origin - Ji, Shujun; Yu, Xiao; Xia, Yufang; Yin, Yifan; Ge, Tingting; Cheng, Lihua; Tian, Cui; Lou, Yanhui (Frontiers in Oncology, 2024)
A 33-year-old young woman with a rare female appendage tumor of suspected Wolffian origin was initially diagnosed with a benign lesion after the resection of a tubal lesion due to the benign cytomorphology of the tumor tissue. However, 1 year after surgery, she was diagnosed with stage IV fallopian tube cancer due to a recurrence, which presented with substantial ascites and invasion of multiple organs, including the bilateral ovaries, intestines, pelvic peritoneum, greater omentum, and appendix. After tumor cytoreduction, the patient responded well to treatment, which included a regimen of platinum-based drugs combined with docetaxel, aromatase inhibitors such as letrozole, antihormonal therapy, and targeted therapy with bevacizumab.